MENGELOLA KAMPUNG DENGAN KEARIFAN LOKAL; Belajar dari Kampung Gampingan di Yogyakarta - Pramudito, Sidhi (Universitas Atma Jaya Yogyakarta, 2017)
Abstract: In recent years many new and modern buildings have emerged in Yogyakarta, on the other hand the existence of kampongs and the natural environment continues to decline, including local wisdom in managing the environment is increasingly abandoned. Kampung Gampingan as a